The Routledge History of American Sport. - Borish, Linda J. (London)
1 online resource (485 pages).
Keywords: "The Routledge History of American Sport provides the first comprehensive overview of historical research in American sport from the early Colonial period to the present day. Considering sport through innovative themes and topics such as the business of sport, material culture and sport, the political uses of sport, and gender and sport, this text offers an interdisciplinary analysis of American leisure. Rather than moving chronologically through American history or considering the historical origins of each sport, these topics are dealt with organically within thematic chapters, emphasizing the influence of sport on American society. The volume is divided into eight thematic sections that include detailed original essays on particular facets of each theme. Focusing on how sport has influenced the history of women, minorities, politics, the media, and culture, these thematic chapters survey the major areas of debate and discussion. The volume offers a comprehensive view of the history of sport in America, pushing the field to consider new themes and approaches as well. Including a roster of contributors renowned in their fields of expertise, this ground-breaking collection is essential reading for all those interested in the history of American sport."--Provided by publisher.